Aggressive Combined Medical and Surgical Management of Mucormycosis Results in Disease Eradication in 2 Pediatric Patients. Issue 3 (August 2017) - Augustine, Haley F. M.; White, Colin; Bain, James
Rhinocerebral mucormycosis is an acute, rapidly fatal, fungal infection, classically involving the nasal mucosa and paranasal sinuses. It is an aggressive, opportunistic infection that frequently progresses to involve the orbit and cerebrum. Cerebral extension in immunocompromised patients is almost universally fatal. There are limited data on mucormycosis in pediatric immunocompromised patients in the literature, with only few reports on rhinocerebral involvement. The immunocompromised patients described in this report presented with suspected periorbital and nasal cellulitis, progressing rapidly to necrotic changes in nasal tissue and oral palatal mucosa. In these patients, the surgical resection of mucormycosis-infected tissue followed by flap reconstruction combined with medical treatment effectively treated the infection, allowed for the rapid resumption of chemotherapy and dramatically improved the quality of life for both the patient and their family.